Intelligent control for ABS application with identification of road and environmental properties. (17th March 2006) - Ivanov, Valentin G.; Algin, Vladimir B.; Shyrokau, Barys N.
The paper discusses conceptual solutions for intelligent algorithms of antilock braking systems (ABS) and other active safety systems. The intelligent control of wheel rolling in braking mode can be organised using the fuzzy logic procedures and statistical regularities of tyre-road interaction, together with the data processing of information from on- and off-board sensors. The possibility for identification of road and environmental properties in a way to create the adaptive, self-learning algorithms is distinctive feature of proposed control strategy. The structure of rules and decision-making procedures for a variant of such control system is presented. The results of simulation are given for the proposed intelligent ABS algorithm, as applied to middle class city bus.